The Performance of Employees in Public Service at Sukadana Village Office Buay Bahuga District Way Kanan Regency - Ibrahim; Aliana Rohmatin Malik; M. Hasbi (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the performance of employees in public service at the Sukadana Village Office, Buay Bahuga District, Way Kanan Regency, Lampung. The research is qualitative with a descriptive approach. The informants consist of 14 individuals, with data collection methods through interviews, observation, and documentation. Data analysis techniques include data collection, presentation, verification, and conclusion drawing. The data validity check was performed using triangulation. Based on the results and discussion regarding employee performance in public service at the Sukadana office, there has generally been an improvement in service quality in various aspects. However, some issues still need to be addressed, such as limitations in facilities and infrastructure, and inconsistencies in employee professionalism. In terms of quantity, the volume of service is considered high, although its implementation is sometimes hindered by time constraints and an unoptimized filing system. Overall, employees have shown responsibility and followed work procedures, although there are still delays in some administrative processes that need attention. Keywords: Controlling, Village Staff Performance, Quality Management